(untitled) (Sains Humanika, 2025)
Cognitive flexibility is the ability to perceive alternatives in various situations, facilitating adaptation and resilience. Given developmental challenges many groups of adolescents face, it is important to ensure the availability of practical, reliable, and valid assessments to measure cognitive flexibility in this population. This study aims to evaluate the psychometric properties of the self-report Cognitive Flexibility Scale (CFS) Indonesian Version for the Indonesian adolescent population. Through convenience sampling approach, 644 adolescents, aged 12 to 18, living in Jabodetabek, completed the Indonesian version of the CFS in a classroom setting. Confirmatory factor analysis tested both unidimensional and two-factor models, revealing superior fit for the two-factor structure. Internal reliability was evaluated using Cronbach’s alpha and McDonald’s Omega, demonstrating adequate reliability (α = 0.72, ω = 0.70). In the second phase, criterion validity was assessed using Spearman’s correlation with the Difficulties in Emotion Regulation Scale - Short Form (DERS-SF) completed by a subsample of 151 adolescents, revealing a significant negative correlation between cognitive flexibility and emotional dysregulation. This correlation underscores the importance of cognitive flexibility in emotion regulation, highlighting its relevance in the context of providing psychological support. Overall, this study supports the CFS Indonesian version as a practical, reliable, and valid instrument for cognitive flexibility assessment among Indonesian adolescents. Future research should focus on more diverse samples to validate the scale further and explore its applicability across different subgroups within Indonesia, especially communities with high social vulnerability.